LIED - Liver: Information, Education and Diagnosis - Console, L.; Molino, G.; di Meana, V. Ripa; Torasso, P. (Methods of Information in Medicine, 1992)
In this paper we describe LIED (Liver: Information, Education and Diagnosis), a diagnostic expert system devoted to medical education in the field of hepatology6. LIED combines the facilities of a traditional expert system for clinical diagnosis with several modules designed for educational purposes. The goal of such modules is to train physicians, in particular as regards the improvement of their problem solving ability (at the end of their curricula students in medicine usually lack experience in organizing an efficient and accurate diagnostic process). Training on real and simulated cases has been widely recognized as a proper approach to clinical experience. The architecture of the diagnostic system is introduced, which forms the core of LIED, and which has been derived from our previous experience, and the various educational functions are discussed that were developed on top of the basic architecture.
Keywords: Artificial Intelligence; Expert Systems; Diagnosis; Educational Systems